BUDAYA “Sulang-sulang Hariapan” Pada Masyarakat Batak Toba Dalam Memaknai Titah Ke-lima - Iwantri Lumbangaol; Albiner Siagian; Rencan C. Marbun (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
Abstract. One of the legacies of the ancestors in the Toba Batak culture is the Manulangi ritual. One of the Manulangi rituals in Toba Batak society is currently known as Sulang-sulang Hariapan. Hariapan toasts in Batak society are known as a way of honoring elderly parents. Respecting parents is an implementation of the fifth law of the Torah contained in Exodus 20:12: